The Influence of Celebrity Endorsers and Social Media Marketing on Purchase Decisions through Brand Image of Le Mineral - Yaumi Rohmah; Ely Siswanto; Ita Prihatining Wilujeng (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
The rapid growth of digital marketing has intensified the use of celebrity endorsers and social media platforms as strategic tools to influence consumer purchasing behavior. This study investigates the influence of celebrity endorsers and social media marketing on purchase decisions, with brand image examined as an intervening variable, focusing on consumers of Le Minerale bottled mineral water in Indonesia. The study is motivated by the consistent increase in Le Minerale’s Top Brand Index from 2021 to 2024, indicating the effectiveness of its marketing strategies amid intense competition in the fast-moving consumer goods (FMCG) industry. A quantitative research design was employed using purposive sampling, involving 180 respondents who had purchased Le Minerale products and actively used social media. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that celebrity endorsers and social media marketing have a positive and significant direct effect on purchase decisions and brand image. However, brand image does not significantly influence purchase decisions and fails to mediate the relationship between celebrity endorsers, social media marketing, and purchase decisions. These results suggest that consumers are more directly influenced by celebrity endorsements and social media exposure rather than by brand image formation. The study contributes to digital marketing literature by highlighting the limited mediating role of brand image in FMCG purchase decisions. Practically, the findings imply that firms should prioritize direct engagement strategies through credible celebrity endorsers and effective social media campaigns to stimulate consumer purchases in the digital era.